Erratum: External validity of the T-SAFT90: A soccer simulation including technical and jumping activities (International Journal of Sports Physiology and Performance, 2022)
TO OUR READERS: An error appeared in the following article: da Silva CD, Lovell R. External validity of the T-SAFT90: a soccer simulation including technical and jumping activities. Int J Sports Physiol Perform. 2020;15(8):1074-1080. PubMed ID: 32814311 doi:10.1123/ijspp.2019-0057